ANALISIS PENGARUH KOMPETENSI,INDEPENDENSI DAN BEBAN KERJA TERHADAP KUALITAS AUDIT DENGAN MOTIVASI SEBAGAI VARIABEL MODERASI (Studi Empiris di Badan Pengawasan Keuangan dan Pembangunan Perwakilan Provinsi Riau) - Dhermawan, Dhermawan; M.Rasuli, M.Rasuli (Jurnal Tepak Manajemen Bisnis, 2018)
Control is a mechanism utilised by executives to ensure that organisationalpolicies and system are well in place to guide the organization to reach its goals. Aninternal auditor is required to possess a certain level of competency and independenceto determine whether the organizationâs (government) work ethics is in compliance tostandard law and regulations. The role of the internal auditor, as part of the APIP inthe Badan Pengawasan Keuangan dan Pembangungan (BPKP) Perwakilan ProvinsiRiau is to produce quality audit result that is able to exert strain on the workload,enabling law enforcers to expose corruption cases in the Riau province. A certain leveland form of motivation is required to ensure that an auditor is able to work to the bestof his or her ability voluntarily. The purpose of this research is to investigate therelationship between independent and dependent variables, moderated by motivation.The research methodology utilizes Partial Least Square with a sample size of ninetythreeauditors from BPKP Perwakilan Provinsi Riau. The reader will be able to formthe following conclusion based on the purpose of the research and area of analysis;competency and independency variables will influence the quality of the auditsignificantly while the workload variable will not influence the audit qualitysignificantly. There is no significant effect between the Motivation as moderationvariable and the competency, independency as well as the work load variable towardsthe quality of the audit.